Menciptakan Lingkungan Pembelajaran Kreatif: Tinjauan Sistematis dalam Pendidikan - Badri Badri; Azisi Azisi (Lembaga Penelitian, Penerbitan dan Pengabdian (LP3M) IAI Al-Urwatul Wutsqo Jombang, 2024)
This research is driven by the urgent need to create a learning environment that not only serves as a place for study but also acts as a space that motivates students, encourages creativity, and enhances their active engagement in the learning process. A creative learning environment has been proven to help students develop critical thinking skills, collaborative abilities, and proficiency in solving complex problems. The purpose of this study is to systematically review the literature to understand the positive impact of a creative learning environment on the field of education. The method used is literature analysis, which includes relevant studies from various trusted sources. The research results show that an innovative and student-responsive learning environment can increase learning motivation while promoting optimal learning outcomes. This study provides valuable guidance for educators and policymakers in designing curricula and teaching methods that support active and participatory learning.